The effect of surface treatment on the shear bond strength of luting cement to a glass-infiltrated alumina ceramic - (:unkn) unknown (QUINTESSENCE PUBL CO INC, 2001)
Purpose: The aim of this study was to evaluate the effect of three different surface treatments on the bond strength of four different luting cements-three bis-GMA-based resin cements and a compomer cement-to In-Ceram. Materials and Methods: Fight In-Ceram samples were used for each experimental group. The samples were randomly assigned three treatment conditions: (1) etching for 90 seconds with 5% hydrofluoric acid gel, (2) sandblasting (110-mum Al2O3), and (3) tribochemical silica coating. All samples were silanated following the surface treatment. The luting cements were bonded to In-Ceram specimens using Teflon tubes. All samples were thermocycled for 5,000 cycles altering between 5 and 55 degreesC with 30-second dwell times. The shear bond strength values were measured in a universal testing machine with a cross-head speed of 1 mm/min, Analysis of variance was used to analyze data. Results: The mean bond strengths varied between 1.2 and 24.7 MPa. Conclusion: Shear bond strength of compomer cement following tribochemical silica coating was significantly lower in comparison to resin cements. Luting of In-Ceram with various resins provided varying degrees of bond strengths that were significantly increased by the tribochemical silica-coating system.
Keywords: COMPOSITE RESIN; DENTAL CERAMICS; PORCELAIN; INTERFACE; REPAIR